Flexible and sensitive piezoresistive electronic skin based on TOCN/PPy hydrogel films. Issue 48 (12th July 2021) - Gao, Yujiao; Liu, Dongning; Xie, Yuanyuan; Song, Yiheng; Zhu, Enwen; Shi, Zhuqun; Yang, Quanling; Xiong, Chuanxi
Abstract: In recent years, the wearable electronic skin (E‐skin) has attracted more and more attention due to high sensitivity, good portability and flexibility. In this work, we used the 2, 2, 6, 6‐tetramethylpiperidinyl‐1‐oxyl (TEMPO)‐oxidized cellulose nanofibril (TOCN) as the substrate, and used the in‐situ polymerization method to introduce polypyrrole (PPy) into the TOCN substrate. Then, the nylon gauze was used as microstructure template to prepare a TOCN/PPy E‐skin with a surface microstructure. This E‐skin possessed excellent sensing and mechanical properties. In the pressure range of 0–600 Pa, the sensitivity of E‐skin was 3.13 kPa −1 . In addition, the E‐skin exhibited ultrafast response/recovery time (≤10 ms), ultralow detection limit of 0.3 Pa, good stability (>9000 cycles) and mechanical strength of up to 117 MPa. Therefore, the TOCN/PPy E‐skin has broad development prospects in the fields of artificial intelligence and health monitoring. Abstract :